1999
DOI: 10.1046/j.1461-9563.1999.00005.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural biological control of the pine processionary moth Thaumetopoea pityocampa (Den. & Schiff.) by the Argentine ant Linepithema humile (Mayr) in Portugal

Abstract: Summary 1 Defoliation by larvae of the pine processionary moth, Thaumetopoea pityocampa, is negligible in stands of Pinus pinaster colonized by the Argentine ant Linepithema humile which preys fiercely on the young moth larvae. In contrast, such damage is widespread where pine plantations are colonized by native ants, predominantly Tapinoma nigerrimum and Lasius niger, which seemingly disregard the larvae. 2 Where L. humile‐ and native ant‐occupied sectors adjoin, there is a 20–50 m overlap in the transition a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Room 1972;Bach 1991;Fernandes et al 2005) or that did not demonstrate a positive correlation between hemipteran density and ant density on plants (e.g. Way et al 1999;Perry et al 2004). We think it is important to note that out of the 30 studies reviewed here, 21 studies (70%) utilized either antexclusion manipulations (nZ19 studies) or natural variation in the presence and absence of ants on plants (nZ2 studies; table 1).…”
Section: Effects Of Ant-hemipteran Interactions On Host Plant Damage mentioning
confidence: 95%
See 1 more Smart Citation
“…Room 1972;Bach 1991;Fernandes et al 2005) or that did not demonstrate a positive correlation between hemipteran density and ant density on plants (e.g. Way et al 1999;Perry et al 2004). We think it is important to note that out of the 30 studies reviewed here, 21 studies (70%) utilized either antexclusion manipulations (nZ19 studies) or natural variation in the presence and absence of ants on plants (nZ2 studies; table 1).…”
Section: Effects Of Ant-hemipteran Interactions On Host Plant Damage mentioning
confidence: 95%
“…Messina 1981;Renault et al 2005), vines, shrubs and trees (e.g. Floate & Whitham 1994;Rico-Gray & Castro 1996;Way et al 1999). In a study of the ant community in the Amazonian rainforest canopy, Blü thgen et al (2000) recorded ant-hemipteran associations on 20 out of 24 tree genera (in 15 tree families) and on 41 out of 66 individual trees surveyed.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates that focusing only on the displacement of ground-dwelling arthropod fauna may lead to an underestimate of the effects of an invasive ant on its adopted community. Moreover, several studies (Styrsky and Eubanks 2007), some with native (Messina 1981, Perfecto andVandermeer 2006) and at least one with invasive ants (Way et al 1999), have reported that ants tending hemipterans sometimes deter herbivores and result in a net benefit or by-product mutualism (Yu 2001) for the plant. To my knowledge this is the first study to report a by-product parasitism of Hemipteratending by an invasive ant.…”
Section: Effects On Floral Arthropods Seed Set and Ovule Predationmentioning
confidence: 99%
“…Ants are known predators of insect eggs (Rossi & Fowler, 2000;Van Mele & Cuc, 2000, 2001Way et al ., 1992Way et al ., , 1999. However, their action was not always beneficial.…”
Section: Discussionmentioning
confidence: 99%